Control, computation and information systems First International Conference on Logic, Information, Control and Computation, ICLICC 2011, Gandhigram, India, February 25-27, 2011. Proceedings - ICLICC 2011 (2011 Gandhigram, India); Balasubramaniam, P.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the International Conference on Logic, Information, Control and Computation, ICLICC 2011, held in Gandhigram, India, in February 2011. The 52 revised full papers presented were carefully reviewed and selected from 278 submissions. The papers are organized in topical sections on control theory and its real time applications, computational mathematics and its application to various fields, and information sciences focusing on image processing and neural networks.
Electronic reproduction.
Keywords: Control theory -- Congresses; Computer logic -- Congresses; Electronic books